2015
DOI: 10.1016/j.psyneuen.2014.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Is depression associated with increased oxidative stress? A systematic review and meta-analysis

Abstract: This meta-analysis finds that oxidative stress, as measured by 8-OHdG and F2-isoprostanes, is increased in depression. Larger-scale studies are needed to extend the evidence on oxidative stress in depression, and examine the potential impact of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
371
3
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 591 publications
(403 citation statements)
references
References 67 publications
18
371
3
11
Order By: Relevance
“…With every double bond, a fatty acid becomes exponentially more susceptible (Assies et al 2014). Of note, many psychiatric disorders manifest themselves together with an increase in oxidative stress, defined as an imbalance between increased free radical formation on the one hand, and decreased anti-oxidant defense on the other (Maes et al 2009;Assies et al 2014;Black et al 2015). This may lead to interesting interactions with fatty acid metabolism (Assies et al 2014) as discussed below.…”
Section: Oxidative Stress Vulnerabilitymentioning
confidence: 99%
“…With every double bond, a fatty acid becomes exponentially more susceptible (Assies et al 2014). Of note, many psychiatric disorders manifest themselves together with an increase in oxidative stress, defined as an imbalance between increased free radical formation on the one hand, and decreased anti-oxidant defense on the other (Maes et al 2009;Assies et al 2014;Black et al 2015). This may lead to interesting interactions with fatty acid metabolism (Assies et al 2014) as discussed below.…”
Section: Oxidative Stress Vulnerabilitymentioning
confidence: 99%
“…Recent studies reported decreased BDNF and increased glia-derived neurotrophic factor (GDNF) levels in both mania and depression (17), increased GDNF/BDNF ratio in mania (18), and increased GDNF levels during manic switch due to ECT (19) confirming the role of the disrupted supportive cellular network in BD. Altered antioxidant enzymes, lipid peroxidation and nitric oxide levels (20)(21)(22), as well as increased DNA damage (23)(24)(25)(26)(27) in BD and a probable coactivation of oxidative damage and repair mechanisms have been reported, particularly in a depressive state of BD (28). Also various inflammatory markers such as TNF-α, interleukin (IL) 1β, IL-6, IL-10, IL-18, IL-4, interferon-γ, monocyte chemotactic protein-1, fibroblast growth factor β, vascular endothelial growth factor, and hs-CRP were reported to be activated in both manic and depressive states of BD (29,30).…”
mentioning
confidence: 99%
“…Alterations in glutathione homeostasis that lead to greater oxidative stress have been implicated in a range of neuropsychiatric and neurodegenerative diseases, including cognitive impairment (Zhao & Zhao, 2013;Baierle et al, 2015;Black et al, 2015). Furthermore, increased oxidative stress can lead to an elevated stress response, and stimulation of apoptosis pathways, resulting in 'sick' cells and ultimately cell death (Townsend et al, 2003).…”
Section: Discussionmentioning
confidence: 99%